Women Empowerment in Lesotho: Reality And/or Myth? - Kali, Moeketsi (International Journal of Scientific Research and Management (IJSRM), 2018)
This paper seeks to challenge the women empowerment policies in Lesotho. It posits that without the transformation of the socio-economic and political sphere, the mechanisms in place cannot lead to real women’s empowerment. It is on this premise that the author suggests that the government of Lesotho needs to resolve the loopholes in the legal system and reconsider its approach and place resources at the disposal of women, in particular, to achieve equality & equity. Unless the laws are amended, until a decisive initiative is taken to reconcile the dilemma and contradiction between the constitution and customary laws and unless the government reinvigorate its commitment, women empowerment, though a reality, will not transcend mediocrity.